Analysis of Green Open Space Availability and Land Surface Temperature Using Multiresolution Imagery in Jember City Area in 2019 and 2024 - Susanti, Devi Ayu Julia; Nurdin, Elan Artono; Astutik, Sri; Pangastuti, Era Iswara (Geosfera Indonesia, 2026)
Green Open Space is an important aspect in regional spatial planning. Lack of availability of Green Open Space can cause environmental problems such as increasing ground surface temperature. The purpose of this study was to analyze the Availability of Green Open Space using Sentinel-2A Imagery in Jember City Area in 2019 and 2024, and to analyze Land Surface Temperature using MODIS Imagery and Sentinel-2A Imagery in Jember City Area in 2019 and 2024. The type of research used is quantitative using a survey method. The sampling technique used purposive sampling with data collection techniques through observation and documentation. The data analysis technique used quantitative descriptive analysis techniques. The research data is presented in the form of a map using the NDVI method for Green Open Space and the LST method for Land Surface Temperature which is processed using Google Earth Engine. The results of this study indicate that the Availability of Green Open Space using Sentinel-2A Imagery in 2024 has been well available, namely 52% of the total area of ​​Jember City, while in 2024 the Availability of Green Open Space was 42% of the total area of ​​Jember City. Furthermore, the results of processing the distribution of Land Temperature using MODIS Imagery and Sentinel-2A Imagery in 2019 and 2024 show that the temperature in the City area is dynamic so that it can change at any time, this is influenced by natural conditions, physical conditions of the area, climate, weather, and hydrology. The highest temperatures tend to be in the city center which then spreads spatially to the outskirts of the Jember City area.